ANTIOXIDANT AND ANTIBACTERIAL ACTIVITIES OF VARIOUS EXTRACTS OF DUKU’S MISTLETOE LEAF (DENDROPHTHOE PENTANDRA (L.) MIQ) COLLECTED FROM MEDAN, INDONESIA - Hardiyanti, Rini; Marpaung, Lamek; Adnyana, I Ketut; Simanjuntak, Partomuan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this research is to evaluate the antioxidant and antibacterial activity of methanol, n-hexane, ethyl acetate, and flavonoid total of Dendrophthoe pentandra (L.) Miq extract. Methods: The leaf of D. pentandra (L.) Miq was gradually extracted using methanol, n-hexane, and ethyl acetate. From that extraction process, various isolates were obtained such as isolate of methanol, n-hexane, ethyl acetate, and flavonoid total. The obtained flavonoid total was continued into separation process using column system with eluent chloroform:methanol in ratio (9:1, 8:2, 7:3, and 6:4) and from this process was obtained six fractions (F1-5). Results: All isolates and fractions that obtained during the extraction and separation process were continued to the activity measurement, such as antioxidant activity using 1,1-diphenyl 2-picrylhydrazyl method and antibacterial activity using agar diffusion method to Salmonella typhi, Pseudomonas sp., Escherichia coli, and Staphylococcus aureus. The antioxidant activity (IC50) of the isolate of flavonoid total and fraction of F4 and F5 was 6.69, 5.98, and 5.95 Î¼g/mL, respectively. On the antibacterial activity, measurement showed a linear correlation between the activity and concentration (10 and 100 Î¼g/mL) of all isolates and fractions. The antibacterial activity was dominated by flavonoid total isolate. Conclusions: The results obtained in this research work showed that the extracts and fractions of D. pentandra (L.) Miq have a potency as antioxidant and antibacterial, especially flavonoid total that acts as antioxidant and fractions F4 and F5 that act as antibacterial.